Financial constraints and the cash-holding behaviour of Canadian firms - Darcey McVanel; Nikita Perevalov (Bank of Canada, 2008)
The proportion of assets held by the average Canadian firm in the form of cash has increased steadily since the early 1990s, and is now roughly twice as large as in 1990. The literature has established that the cash-holding behaviour of firms is highly correlated with financial constraints and firm characteristics. The authors use a firm-level data set covering Canadian firms from 1980 to 2006 to understand which firm characteristics are associated with higher cash holdings. They find that financial constraints are likely important for explaining firms' higher cash holdings, and that the recent increase in the cash holdings of Canadian firms can be almost entirely explained by changes in firm characteristics. Specifically, higher recent cash holdings are correlated with the average Canadian firm having become smaller, having more variable cash flow, holding lower levels of cash substitutes, having higher expenditure on research and development, and being more likely to be financially distressed. The authors also find that the average Canadian firm has a cash ratio that is only slightly higher than would be predicted by out-of-sample forecasts over the 1990s and 2000s, though the divergence between the actual and predicted values has been increasing in recent years.
Keywords: G11; G32; 330; Sectoral balance sheet; Betriebliche Finanzwirtschaft; Betriebliche Liquidität; Cash Management; Finanzmarkt; Verschuldungsrestriktion; Kanada